2019
DOI: 10.3389/fnins.2019.00119
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Neuromodulation in Acute Spinal Cord Injury via Transcutaneous Tibial Nerve Stimulation: Cystometrogram and Autonomic Nervous System Evidence From a Randomized Control Pilot Trial

Abstract: Aim: Percutaneous tibial nerve stimulation is used to decrease incontinence in chronic neurogenic bladder. We report the findings from a subset of patients in a randomized control trial of transcutaneous tibial nerve stimulation (TTNS) for bladder neuromodulation in acute spinal cord injury (SCI) in whom heart rate variability (HRV) was recorded before and after cystometrogram (CMG). The aim was to correlate autonomic nervous system (ANS) changes associated with the CMG changes after the trial using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 26 publications
0
18
0
2
Order By: Relevance
“…Related to The rationale behind SCS activity at neurovegetative functions is still unknown. Preliminary evidence suggests that transcutaneous tibial nerve stimulation in acute spinal cord injury is able to achieve bladder neuromodulation via modulation of autonomic nervous system functions [14], however it needs further studies. For example, incontinence in women with lumbar spinal canal stenosis is significantly different from the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Related to The rationale behind SCS activity at neurovegetative functions is still unknown. Preliminary evidence suggests that transcutaneous tibial nerve stimulation in acute spinal cord injury is able to achieve bladder neuromodulation via modulation of autonomic nervous system functions [14], however it needs further studies. For example, incontinence in women with lumbar spinal canal stenosis is significantly different from the control group.…”
Section: Discussionmentioning
confidence: 99%
“…[ 142 ] Bladder neuromodulation in acute spinal cord injury via transcutaneous tibial nerve stimulation: cystometrogram and autonomic nervous system evidence from a randomized control pilot trial Stampas et al. [ 143 ] Lower urinary tract dysfunction in the neurological patient: clinical assessment and management Panicker et al. [ 144 ] Neuromodulation by surface electrical stimulation of peripheral nerves for reduction of detrusor overactivity in patients with spinal cord injury: a pilot study Ojha et al.…”
Section: Electrical Simulationmentioning
confidence: 99%
“…A randomised pilot trial in patients with acute SCI concluded that TTNS was feasible and safe in an inpatient rehabilitation setting. 29 Furthermore, at the end of the study, the participants in the intervention group had lower detrusor pressures and fewer developed DSD compared with the sham group, 30 suggesting that TTNS could alter the course of NLUTD. We hypothesise that TTNS applied in the acute phase after SCI will prevent the emergence of C-fibre evoked bladder reflexes, thereby the development of NDO, and avert UUT damage and urinary incontinence.…”
Section: Introductionmentioning
confidence: 99%